The commercial aircraft finance handbook - Scheinberg, Ronald (New York: Routledge, 2018)
"The Commercial Aircraft Finance Handbook is a resource for every type of aircraft finance practitioner - seasoned and starter alike. The handbook offers a complete view of the process of aircraft financing and the myriad issues that can arise, clearly explaining terminology as it works through the steps. It can be used as both a learning aid and resource book to be referred back to again and again. The area of aircraft finance is multidisciplinary (touching professionals across law, finance, insurance, leasing to name a few) and this book arms these diverse individuals with a framework for knowing what questions and issues should be considered in a given situation. It does not aim to make them experts in an area outside of their particular expertise but to understand the perspectives in the "other" disciplines within aircraft finance. This book will provide juniors with an introduction to the myriad of topics in aircraft finance and provide seniors with explanations of matters outside their normal area of expertise, as well as provide seasoned practitioners with the resources provided in the appendices"--
Aircraft and other aircraft finance assets/collateral -- Deal types, structures and enhancements -- Pricing provisions -- Aircraft/engine terms -- Maintenance/return conditions -- Legal -- Bankruptcy/workouts/remedies -- Insurance -- Valuation -- Contracts and instruments -- Special contractual provisions.
Includes bibliographical references.
Keywords: Aeronautics, Commercial -- Finance